STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN EFEKTIVITAS KERJA GURU PADA MADRASAH TSANAWIYAH MIFTAHUL ULUM LIMBUR TEMBESI KABUPATEN SAROLANGUN - Rahmanita, Rika; Rusmini; Yunus, Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Leadership plays a crucial role in influencing, guiding, and directing individuals or groups to achieve educational goals effectively. However, teacher work effectiveness in madrasahs is often influenced by leadership strategies, availability of facilities, workload, and teacher motivation. This study aims to analyze the effectiveness of teachers’ work, identify the obstacles faced by the principal, and examine the strategies implemented to improve teacher work effectiveness at MTs Miftahul Ulum Limbur Tembesi, Sarolangun Regency. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving selected informants and respondents to obtain an in-depth understanding of the phenomenon. The results show that teacher work effectiveness is generally good, as teachers have carried out their responsibilities in lesson planning, implementing interactive learning, and evaluating student learning outcomes. Nevertheless, several obstacles were identified, including limited learning facilities and infrastructure, high teacher workload, and insufficient motivation among some teachers to develop professionally. To address these challenges, the principal implemented various managerial and leadership strategies, including supervision, professional guidance, motivation, and efforts to improve the learning environment, which contributed to enhancing teacher work effectiveness.